Competitive Advantage Strategy Management of Private Schools in Southeast Maluku Regency: A Case Study of Schooling at the Johanis Ars College in the Kei Kecil Region - Yohanis Paulus Namsa; Jeffry Sony Junus Lengkong; Ruth Umbase; Parabelem Tinno Dolf Rompas (JR Education, 2026)
The strategic management of competitive advantage in private schools is the main focus of this study to address the dynamics of competition in educational institutions in Southeast Maluku Regency. The main objective of the study is to formulate an adaptive school management model under the auspices of Kolose Johanis Ars to address fluctuating student numbers and limited resources in the archipelago. A descriptive qualitative approach was used as a method to explore the management phenomenon in depth through interviews, observations, and documentation studies at the research site in the Kei Kecil region. The research subjects included the principal, teachers, and relevant stakeholders directly involved in the strategic decision-making process. The research findings indicate that a differentiation strategy based on spiritual values ​​and social capital is a significant internal strength for the school, but there are still weaknesses in aspects of technological innovation and digitalization of learning. The analysis results identified a gap in contextual curriculum adaptation where the local maritime potential of the Kei region has not been optimally integrated into the school curriculum. The research conclusions emphasize the need for dynamic capability reconfiguration through strengthening the management information system and synchronizing the college's long-term vision with operational plans at the school unit level. The proposed management model integrates resource-based theory with spiritual leadership to ensure the sustainability of educational institutions in the outermost regions. Implementing a systematic marketing strategy and improving the digital literacy of educators are practical recommendations for strengthening schools' bargaining power in the eyes of the public. Synergy between foundations, local governments, and local communities is essential for sustainably improving the quality standards of educational services.